My Voice Capturing My Attention to Myself: The Effects of Objective Self-Awareness on Japanese People - Narita, Asuka; Ishii, Keiko (Frontiers in Psychology, 2020)
Previous research demonstrated that the presence of a mirror does not influence Japanese people’s self-evaluation and cheating behaviors, which reflects their tendency to habitually think themselves based on their imagined perspectives of others. The present work extends the evidence by manipulating the presence of the participants’ own voices as well as that of a mirror (Study 1); it explores the effects of another participant’s voice (Study 2). Consistent with previous findings, the presence of a mirror does not influence Japanese participants’ self-esteem, moral values, and cheating behaviors. In contrast, the impact of their own voice was partially found. The exposure to their own voice decreased the participants’ moral value of fairness and discouraged the participants from cheating by drawing additional coins. Furthermore, no effect of other voice was found. Overall, we observed a limited effect of self-focusing stimuli in Japanese participants, although it should be noted that their own voice was relatively effective for capturing self-focused attention.